ANALYSIS OF THE IMPLEMENTATION OF NON-COMMUNICABLE DISEASES INTEGRATED HEALTH AT UPT PURUK CAHU HEALTH CENTER - Fatimah Herlinawati; Achmad Rizal; Mahmudah Mahmudah; Eddy Rahman (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2024)
To control non-communicable diseases, the NCD Posyandu (integrated service post) monitors and detects possible risk factors for non-communicable diseases in the community. This study used qualitative research methods with in-depth interview questionnaires for informants at the NCD Posyandu, UPT Puruk Cahu Health Center. The study’s results comparing the NCD Posyandu implementation standards for 2014 showed that the NCD Posyandu work area had good and competent cadres, with patients getting NCD services and counseling for free. Recommendations are needed to improve partnerships, funding support, and NCD Posyandu implementation tools, increase the number of cadres, and provide training to all NCD Posyandu cadres and meetings for the community on non-communicable diseases so that coordination among all parties in NCD Posyandu, including the community, runs optimally both in quality and quantity.